Managing tourism in South Africa - George, Richard; Alida Terblanche, Gavin Barfield, Marisa Montemarano, Marcus Bester, Sharna Sammy, Sharna Sammy, John Hall, Tanya Barben, Photo Access, OUP Classet, Image of Africa (Cape Town ; New York : Oxford University Press Southern Africa, 2007)
Summary: "Managing tourism in South Africa equips students as well as practitioners with a combination of industry-specific knowledge and general managerial skills needed to succeed. It explores the fundamental business management aspects of tourism including law, management, human resource management, marketing, and finance, and shows how the industry is structured."--Jacket
Includes bibliographical references and index.
Adult
Keywords: South Africa; Case studies